Two new species of Castiarina Gory and Laporte, 1838 (Coleoptera: Buprestidae: Stigmoderini) from Australia - Hutchinson, Paul M.; Allsopp, Peter G. (Zootaxa, 2022)
Two new species of Castiarina Gory & Laporte, 1838 (Coleoptera: Buprestidae: Stigmoderini) are described from Australia. Castiarina testudocaput sp. n. is recorded from Turtle Head Island off the tip of Cape York Peninsula, northern Queensland, whilst Castiarina notocrux sp. n. is recorded from southern Western Australia. Characters distinguishing them from other species of Castiarina are discussed.